TRADISI KATOBA: KEARIFAN LOKAL MASYARAKAT MUNA SEBAGAI UPAYA PENCEGAHAN KEKERASAN SEKSUAL TERHADAP ANAK DI KOTA KENDARI - Rivi Handayani; La Ode Sahidin; Sitti Haerani Idrus (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study offers a method based on local wisdom of Muna society in Kendari City. When the children enter the age of 7-12 years, parents are required to organize Katoba rituals. Katoba ritual is a means to deliver and guide the child into the early phase of adult life. The content of the values in the katoba becomes the basic of early age, adult, even to the old age. Starting from the age of the children (after doing the ritual of katoba) until he is mature, then he has immoral acts, sentences that come out from the society